Preference Analysis of Employer Attractiveness: What Do Final Year Students Consider Important? - Olivia Cindy Pandora; Nia Ariyani Erlin (Pusat Studi Pembangunan dan Pemberdayaan, 2025)
Employer attractiveness is one of the factors considered when choosing a place to work. However, previous studies did not explain in detail which attributes of employer attractiveness were considered most important when applying to a company. This study aimed to determine the preferences of final-year students as prospective employees regarding the attributes of employer attractiveness. Five attributes were used in this study: interest, social, economic, development, and application. This study employed a descriptive quantitative method involving 150 respondents, who were final-year students from the Bachelor of Management and Bachelor of Accounting programs, selected using purposive sampling. Data were collected using a questionnaire and analyzed using SPSS 26 software. Of the 150 respondents, only 148 respondents' data could be processed. The results of this study indicated that the attribute most considered important and aligned with respondents' preferences was the economic attribute, with an importance value of 38.684. The level of the economic attribute most preferred by respondents was a company that provided salaries commensurate with employee performance, with a utility estimate value of 0.322. The combination or stimuli that were of interest and considered important by respondents included companies that supported employee creativity, had a healthy and enjoyable work environment, provided salaries commensurate with employee performance, offerred training and development programs, and maintained high-quality customer service and hospitality.